Screening the carotenoid in vitro bioaccessibility of purple corn breakfast cereal consumed with milk and plant-based milk - Salvador-Reyes, Rebeca (2024)
Chronic non-communicable diseases (NCD), such as cardiovascular diseases, diabetes, and cancer, dominate global mortality, besides compromising the quality of life. Unhealthy habits like sedentary lifestyles and poor diets escalate NCD risks. Conversely, the consumption of phenolic compounds and carotenoids has shown promise in reducing NCD risks. The food industry responds by adapting products to meet demands for healthier options rich in bioactive compounds. For instance, breakfast cereals made from purple and yellow corn offer carotenoids and anthocyanins and form a nutrient-balanced meal when consumed with milk or alternatives. However, bioactive compounds in food do not guarantee absorption, necessitating bioaccessibility studies. In this study, we aimed to evaluate the bioaccessibility of the major carotenoids in two breakfast cereals, one made with 100% yellow corn and the other with 50% purple corn, co-digested with whole milk, semi-skimmed milk, skimmed milk, and almond “milk”. The bioaccessibility of lutein in the breakfast cereals was evaluated using the INFOGEST 2.0 in vitro digestion method. Results showed that lutein bioaccessibility ranged from 9% to 29%. The bioaccessibility was lower than that observed in other food matrices, such as spinach and maize products. High fiber, low carotenoid contents, and anthocyanin presence negatively influenced the carotenoid bioaccessibility. Interestingly, the varying lipid content of milk showed no impact on lutein bioaccessibility under the examined conditions. In conclusion, the effects of lipids in a low range (0–7%) are not significant (p > 0.05) compared to other matrix components. When developing new products with health and nutritional benefits, it is important to consider that while fiber can reduce the bioaccessibility of carotenoids, it remains crucial for gut health.